Peer-to-peer in the workplace: A view from the road - Ishtiaque Ahmed, Syed; J. Bidwell, Nicola; Zade, Himanshu; Hulikal Muralidhar, Srihari; Dhareshwar, Anupama; Karachiwala, Baneen; N. Tandong, Cedrick; O'Neill, Jacki (CHI Conference on Human Factors in Computing Systems, 2016)
This paper contributes to the growing literature on peer-to-peer (P2P) applications through an ethnographic study of auto-rickshaw drivers in Bengaluru, India. We describe how the adoption of a P2P application, Ola, which connects passengers to rickshaws, changes drivers work practices. Ola is part of the ‘peer services’ phenomenon which enable new types of ad-hoc trade in labour, skills and goods. Auto-rickshaw drivers present an interesting case because prior to Ola few had used Smartphones or the Internet. Furthermore, as financially vulnerable workers in the informal sector, concerns about driver welfare become prominent. Whilst technologies may promise to improve livelihoods, they do not necessarily deliver [57]. We describe how Ola does lit-tle to change the uncertainty which characterizes an auto drivers’ day. This leads us to consider how a more equitable and inclusive system might be designed.